Paper 22: PREDICTORS OF RE-OPERATION IN ADOLESENTS UNDERGOING HIP PRESERVATION SURGERY FOR FEMOROACETABULAR IMPINGEMENT. Issue 7 (30th July 2022) - Cooper, Savannah; Johnson, Benjamin; Youngman, Tyler; Wilson, Philip; Sucato, Daniel; Podeszwa, David; Ellis, Henry; Serbin, Philip
Objectives: Femoroacetabular Impingement(FAI) is a condition caused by repetitive motion of abnormal hip osseous anatomy that contributes to labral and chondral injury. An understanding of radiographic parameters associated with successful primary surgery has not been well established. The primary objective was to determine pre-operative radiographic parameters that predict reoperation for FAI and, secondarily, correlate radiographic measures and outcomes in these patients. Methods: A prospectively-collected institutional registry of adolescent patients (age <19 y.o.) who underwent surgery for FAI (arthroscopic/open) was reviewed. Standing AP pelvis X-rays were analyzed for alpha, lateral center edge(LCEA), Tönnis, and Sharp's angles, and femoro-epiphyseal acetabular(FEAR) index. Patient-reported outcomes(PROs) [modified Harris Hip Score (mHHS), Hip Disability and Osteoarthritis Outcome Score(HOOS)] were analyzed. Mann-Whitney-U test was used to compare the radiographic measures of re-operation to non-reoperation patients and those who achieved MCID to those who did not. Radiographic indication of risk for re-operation was evaluated with receiver operating characteristic(ROC) analysis. Spearman's correlation was calculated between radiographic measurements and PROs at 2-years post-op. Results: Eighty-seven patients underwent primary surgery (56 surgical dislocations vs 31 scopes) for FAI. The average age at time of primary operation was 16.27 years(73.6%Female). 10 underwent re-operation (11.5%) at an average of 20.6 months from primary surgery. No differences were found in demographics, activity, surgery type, labral disease, or alpha angle for re-operation vs. non-reoperation. The LCEA, FEAR Index, Sharps, and Tönnis angle were significantly different (p<0.05) (Table 1). ROC analysis indicated that LCEA<21 and FEAR index>-8.8 were predictors for increased risk of reoperation. Patients with LCEA<21°, 46% underwent a reoperation compared to those with LCEA>21° (6%). Patients with FEAR index<-8.8, 32% underwent a reoperation compared to patients>-8.8 (5%). Patients who achieved MCID (61.9%) had lower BMI, worse pre-operative PROs, and better post-operative PROs at 2-years. Alpha, Tönnis, and Sharp's angles were positively correlated with 2+ year PROs, while LCEA was negatively correlated(p<0.05). Conclusions: In patients undergoing treatment for FAI, a reoperation was associated with radiographic signs of hip dysplasia, indicating that patients with a shallower acetabulum are at risk for a repeat operation. Surgeons can utilize these parameters to help in surgical decision making, better predict outcomes and to counsel patients the need for potential subsequent surgery. UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/10177e80-b6a8-458e-b216-840ad950f2a6/1/Tables.docx